134k views
5 votes
3. Which of the following is equivalent to 3(y – 1 + 2y)? A. 3y – 9 B. 6y – 3 C. 9y – 3 D. 3y – 3

User Steve Ross
by
5.7k points

2 Answers

5 votes

Final answer:

To solve the equation 3(y - 1 + 2y), distribute the 3 to each term inside the parentheses, combine like terms, resulting in 9y - 3.

Step-by-step explanation:

To solve the equation 3(y - 1 + 2y), we need to distribute the 3 to each term inside the parentheses:

3 × y = 3y

3 × -1 = -3

3 × 2y = 6y

So the equation becomes 3y - 3 + 6y. Combining like terms, we get 9y - 3. Therefore, the correct equivalent expression is 9y - 3 (Option C).

User Davidkonrad
by
6.0k points
3 votes

Answer:

y = 1/3

Step-by-step explanation:

3(y – 1 + 2y)

= 3y - 3 + 6y

= 3y + 6y - 3

= 9y -3

9y = 3

y = 3/9

y = 1/3

User Aug
by
5.1k points